Factors Affecting Self-determination in Mathematic Learning of Thai Grade 8 Students - Nattapon Yotha; Kasemsan Rojchaphot (Journal of Educational Issues, 2024)
The purposes of the study were to investigate the relationship between factors and self-determination in learning mathematics of grade 8 students in Thailand and to study factors affecting self-determination in learning mathematics of grade 8 students. The participants were 500 students in an area called Bueng Kan province in Thailand. They were selected using multi-stage random sampling from the population of 872 grade 8 students in the area. The instrument was an assessment of grade 8 students’ self-determination in learning mathematics. The assessment consisted of 70 items assessing factors that could affect students’ self-determination and 30 items assessing students’ self-determination in learning mathematics. The assessment items were proved with 0.34-0.62 discrimination and 0.96 reliability. The data were analyzed using percentages, mean scores, standard deviation, and Stepwise Multiple Regression Analysis. The variables used in the data analysis were intrinsic motivation (X1), attitude toward mathematics (X2), learning behaviors (X3), teacher instruction technique (X4), teacher-student relationship (X5), problem-solving abilities (X6), and social support (X7) as predictions while self-determination in mathematics learning (Y) was set as the criterion. The results of the study indicate that the Stepwise Multiple Regression Analysis indicates 4 factors including intrinsic motivation, learning behaviors, teacher instruction technique, and the teacher-student relationship showing a correlation to self-determination in learning mathematics. Moreover, the predictable factors were intrinsic motivation (X1), learning behaviors (X3), teacher instruction technique (X4), and teacher-student relationship (X5). They could predict approximately 76.00% of self-determination. The predictable equation in raw scores and standard scores were, Y’ = 0.06 + 0.52X1 + 0.27X3 + 0.09X5 + 0.12X4; Z’s = 0.53Z1 + 0.26Z3 + 0.11Z5 + 0.13Z4.